A Gene Transfer-Positive Cell Sorting System Utilizing Membrane-Anchoring Affinity Tag - Yang, Lele; Cui, Lifang; Ma, Shumin; Zuo, Qingqing; Huang, Qilai (Frontiers in Bioengineering and Biotechnology, 2022)
Gene delivery efficiency is an essential limit factor in gene study and gene therapy, especially for cells that are hard for gene transfer. Here we develop an affinity cell sorting system that allows efficient enrichment of gene transfer-positive cells. The system expresses an enhanced green fluorescent protein (EGFP) fused with an N-terminal high-affinity Twin-Strep-Tag (TST) that will be anchored to the cell membrane at the out-surface through a glycosylphosphatidylinositol (GPI) membrane-anchoring structure. The EGFP permits microscopy and flow cytometry analysis of the gene transfer-positive cells, and the TST tag at the N terminal of EGFP allows efficient affinity sorting of the positive cells using Strep-Tactin magnetic beads. The cell sorting system enables efficient isolation of gene transfer-positive cells in a simple, convenient, and fast manner. Cell sorting on transfected K-562 cells resulted in a final positive cell percentage of up to 95.0% with a positive cell enrichment fold of 5.8 times. The applications in gene overexpression experiments could dramatically increase the gene overexpression fold from 10 times to 58 times, and in shRNA gene knockdown experiments, cell sorting increased the gene knockdown efficiency from 12% to 53%. In addition, cell sorting in CRISPR/Cas9 genome editing experiments allowed more significant gene modification, with an editing percentage increasing from 20% to 79%. The gene transfer-positive cell sorting system holds great potential for all gene transfer studies, especially on those hard-to-transfect cells.